Qualitative exploration of nurses' perspectives on clinical oxygen administration in Ghana - Faustina Excel Adipa; Lydia Aziato; Ahmed N. Zakariah (Elsevier, 2015)
Background: Oxygen therapy is an integral part of emergency and immediate post-operative management. Objectives: The study sought to gain full understanding on nurses' perspectives on clinical administration of oxygen within the emergency and immediate post-operative environment. Methods: The study employed a descriptive qualitative design to achieve its objectives. The study was conducted at the adult emergency unit, Surgical Medical Emergency, and the Cardiothoracic Intensive Care Unit of the Korle-Bu Teaching Hospital (KBTH). The target population was nurses. A purposive sample of 12 nurses; six from each unit were involved in the study. Data was collected through individual face-to-face interviews which were audiotaped and transcribed verbatim. Data was analyzed concurrently applying the principles of content analysis. Results: Themes generated on commencement and monitoring of oxygen therapy included initiation of oxygen therapy, and assessment and monitoring of patient. Other themes on challenges of oxygen therapy were knowledge and information gap, lack of protocol, availability and cost of delivery devices, and oxygen supply. Conclusion: Nurses require further training in oxygen therapy and there is the need to develop appropriate protocols to guide oxygen therapy.